A comparative study of Hasford score and Sokal index in prognostication of the novo chronic myeloid leukemia patients and a search for new prognostic markers - Swapan Kumar Sinha; Simanti Sinha; Palash Kumar Mandal; Nirmal Kumar Bhattacharyya; Abhigyan Pandey; Partha Gupta (Wolters Kluwer Medknow Publications, 2013)
Introduction: Chronic myeloid leukemia (CML) is a common myeloproliferative disorder. Based on clinical and hematological parameters, two prognostic scoring systems, i.e., Hasford and Sokal index scoring systems are available to predict survival duration of CML patients on imatinib therapy. Aims and Objectives: Our study's objective is to compare Hasford score with Sokal index for the prognostication of de novo CML patients on therapy and find out new prognostic markers. Materials and Methods: This is a retrospective study. The study population comprised 66 patients who were followed up for 60 months. For each patient, at presentation, scoring was performed as per Hasford and Sokal index and Philadelphia chromosome analysis was carried out by conventional cytogenetics. Thereafter, hematological parameters were assessed 3 monthly and conventional cytogenetics was done yearly. Results: Out of these 66 patients, the number of patients belonging to low, intermediate and high risk categories are 21, 33 and 12 respectively by Hasford score and 12, 32 and 22 respectively by Sokal index. Eight patients, who had been categorized into high risk group by Sokal index but intermediate risk group by Hasford score, have shown better survival possibility as monitored by hematological and cytogenetic parameters. Ten cases, categorized into intermediate risk group by Sokal index but low risk group by Hasford score, is doing well till date. Conclusions: This study shows that Hasford score predicts survival of the patients better than Sokal index. However, multicentric study over a large population is needed to give the final verdict.